Molecular Pathology Protocols - Killeen, Anthony A.; Killeen, Anthony A. (Methods in Molecular Medicine, 2001)
Because molecular pathology has only recently emerged from the laboratory, many molecular pathology protocols are still to be found only in the primary literature. In Molecular Pathology Protocols, Anthony Killeen has assembled a collection of readily reproducible molecular pathology techniques that are either frequently performed or recognized for their significant diagnostic utility. Each method is described in step-by-step detail by a leading molecular pathologist or laboratory scientist who has developed it or used it extensively. These clinical laboratory techniques can be used for the diagnosis or monitoring of cancer, hematological malignancies, infectious diseases, and selected genetic disorders. Cutting-edge methods include telomerase, microsatellite instability, chromosomal translocations, and fluorescent in situ hybridization assays. Time-tested practices and numerous tips on how to avoid pitfalls ensure robust and successful results. Comprehensive and path-breaking, Molecular Pathology Protocols will enable clinical laboratories to introduce new molecular pathology tests and lay the groundwork for a much-needed standardization in this rapidly developing field.